Hepatitis B Virus X Protein Increases the Cdt1-to-Geminin Ratio Inducing DNA Re-replication and Polyploidy - Rakotomalala, Lova (American Society for Biochemistry and Molecular Biology, 2008)
Hepatitis B virus X protein (pX) is implicated in hepatocellular carcinoma pathogenesis by an unknown mechanism. Employing the tetracycline-regulated pX-expressing 4pX-1 cell line, derived from the murine AML12 hepatocyte cell line, we demonstrate that pX induces partial polyploidy (>4N DNA). Depletion of p53 in 4pX-1 cells increases by 5-fold the polyploid cells in response to pX expression, indicating that p53 antagonizes pX-induced polyploidy. Dual-parameter flow cytometric analyses show pX-dependent bromodeoxyuridine (BrdUrd) incorporation in 4pX-1 cells containing 4N and >4N DNA, suggesting pX induces DNA re-replication. Interestingly, pX increases expression of endogenous replication initiation factors Cdc6 and Cdtl while suppressing geminin expression, a negative regulator of rereplication. In comparison to a geminin knockdown 4pX-1 cell line used as DNA re-replication control, the Cdt1/geminin ratio is greater in 4pX-1 cells expressing pX, indicating that pX promotes DNA re-replication. In support of this conclusion, pX-expressing 4pX-1 cells, similar to the geminin knockdown 4pX-1 cells, continue to incorporate BrdUrd in the G(2) phase and exhibit nuclear Cdc6 and MCM5 co-localization and the absence of geminin. In addition, pX expression activates the ATR kinase, the sensor of DNA re-replication, which in turn phosphorylates RAD17 and H2AX. Interestingly, phospho-H2AX-positive and BrdUrd -positive cells progress through mitosis, demonstrating a link between pX-induced DNA re-replication and polyploidy. Our studies high-light a novel function of pX that likely contributes to hepatocellular carcinoma pathogenesis.